(untitled) (Annals of Medical Research, 2021)
Aim: The main purpose of this study was to research short-term wound-related results and complications of tension-free hernia repair, especially in the postoperative period during the length of stay in the hospital (LOS).Materials and Methods: This study had a retrospective design. Study data was collected via the 29 Mayıs State Hospital registry system. Between May 30, 2016, and May 30, 2019, a total of 1128 cases were screened. Patients were identified who were operated for tension-free inguinal hernioplasty. In total, 652 patients were included in this study. Patients with inconsistent diagnostic data, no documentation of seatbelt use, or missing outcomes were excluded. For descriptive statistical analyses, the mean and standard deviation were used for continuous variables, and percentage and frequency values were used for dichotomous variables. The statistical tests were chosen according to the Kolmogorov Smirnov test. After univariate analysis, the final statistical results were done with multiple binary logistic regressions. A 5% level was chosen as significant for p-values. Data were analysed with SPSS™ for Windows 18 (SPSS, Chicago, IL). Patient demographics, hernia side, hospital LOS, body mass index (BMI) and postoperative complications were abstracted for each patient.Results: The total number of patients is 652 [males: 619 (94.9%) vs. females: 33 (5.1%)]. The mean age of both males and females was 56.83 ± 14.3 years and 57.33 ± 11.4 years (p = .84), respectively. For both males and females, the mean BMI was 24.09 ± 6.54 kg/m2 (24.12 ± 6.51 kg/m2 vs. 23.32 ± 7.07 kg/m2).The mean duration of LOS was detected as 2.45 ± 1.02 days. In the LOS period, prominently, BMI (30 kg/m2) and incarcerated-strangulated hernias were found highly significant for seroma, in statistical analysis with multiple binary logistic regression analysis [AOR: 4.3 (1.3, 13.8) (p ≤ .05)] and [AOR: 12.1 (4.9, 29.5) (p ≤ .05)], respectively.Conclusion: For patients who have a BMI above 30 kg/m2 and especially for strangulated or incarcerated hernias, the seroma complication may be a candidate.Keywords: Lichtenstein; wound related; postoperative early complications.